A Case Report of Mycoplasma pneumoniae-induced fulminant myocarditis in a 15-year-old male leading to cardiogenic shock and electrical storm - Zhu, Chengrui; Hu, Bo; Li, Xiaotong; Han, Weiying; Liang, Yingjian; Ma, Xiaochun (Frontiers in Cardiovascular Medicine, 2024)
Mycoplasma pneumoniae (M. pneumoniae) is a well-recognized pathogen primarily associated with respiratory tract infections. However, in rare instances, it can lead to extrapulmonary manifestations, including myocarditis. We present a case of a 15-year-old male who developed fulminant myocarditis, cardiogenic shock, and cardiac electrical storm attributed to M. pneumoniae infection. He underwent a combination of iIntra-aAortic Bballoon Ppump (IABP) and Vveno-Aarterial Eextracorporeal Mmembrane Ooxygenation (VA-ECMO) for cardiac support, ultimately surviving despite the intracardiac thrombus formation and embolic stroke. Following comprehensive treatment and rehabilitation, he was discharged in stable condition. This case underscores the importance of considering atypical pathogens as potential etiological factors in patients presenting with cardiac complications, especially in the adolescents. It also emphasizes the need for clinical vigilance and effective support for potential cardiac complications arising from M. pneumoniae infection.